Análise da influência da corrente marítima na remoção dos sedimentos no Terminal Marítimo Ponta da Madeira em São Luís – MA - FIGUEIREDO, Alexandre Ramos de (2018)
The Ponta da Madeira Maritime Terminal is composed of three piers with an average depth of 25 meters, which allows the mooring of a large draft. However, the piers are located in regions of intense sedimentary dynamics, these areas being subject to silting processes, which require frequent dredging activities. To ensure adequate depths for port operations, Vale has been carrying out dredging for more than 30 years to maintain this terminal. The objective of this work was to analyze the hydrodynamic and sedimentological behavior of Pier IV Norte of the Maritime Terminal of Ponta da Madeira. It has as purpose to analyze the hydrodynamic and sedimentological behavior and its impacts on the operation of the Pier from research in Field, survey and historical analysis of the bathymetric data; monitoring of the Sequence of Construction - Pier 4 Norte the influence of the cutting of the stakes in the erosion of the seabed (process of construction of the pier) and the movement of sediments; define minimum depths to be maintained as a function of the project vessel and evaluate the dredging strategy to minimize operational impacts. Before the preliminary data analysis (LH), it allows identifying the impact of keeping the ship berthed and loaded under extreme operational conditions. It was necessary to define routine with dedicated team building for LH, bathymetry processing and analysis, as well as a guide for dredging interventions and to optimize the volume demand for dredging that impacts the hours of use of the pier. The continuity of the sedimentation study with frequent hydrographic surveys provides a better understanding of the behavior of sedimentation dynamics since the minimum depths to be maintained for the project vessel (VMAX) require evaluating the best dredging strategy to minimize operational and financial impacts.